Efficacy and safety of Chinese medicines for asthma: A systematic review protocol. Issue 34 (August 2019) - Shi, Qi; Si, Dongxu; Bao, Haipeng; Yan, Yue; Kong, Yanhua; Li, Chunlei; He, Wenfeng; Damchaaperenlei, Dashzeveg; Yu, Mingxia; Li, Youlin
Abstract: Background: Asthma is a complex disease associated with many factors such as immunologic, environmental, genetic, and other factors. Common medicines used to treat asthma include β-agonist and glucocorticoid. However, in the long-term treatment, the effect of the above-mentioned drugs is not satisfactory, so many patients choose oral Chinese medicines instead of western medicines. The introduction of Chinese medicines therapies, a rapid proliferation of the literature on management of asthma in general, call for novel ways of evidence synthesis in this area. This systematic review is to systematically summarize and evaluate a large number of evidences for Chinese herbal interventions for asthma. Evaluate the efficacy and safety of Chinese medicines in the treatment of asthma and inform a decision aid for the clinical encounter between patients and clinicians. In addition, it helps to establish a future research agenda. Methods: Five English databases (PubMed, Web of science, EBASE, Springer Cochrane Library, and WHO International Clinical Trials Registry Platform) and 4 Chinese databases (Wanfang Database, Chinese Scientific Journal Database, China National Knowledge Infrastructure Database, and Chinese Biomedical Literature Database) will be searched normatively according to the rule of each database from the inception to the present. The literature screening, data extraction, and quality assessment will be conducted by 2 researchers independently. Data will be synthesized by either the fixed-effects or random-effects model according to a heterogeneity test. Asthma control test symptom score will be assessed as the primary outcome. The curative effect of single symptom and sign; Withdrawal and reduction of western medicines in a course of treatment, including: time, type, and quantity; Maintenance of western medicines after the course of treatment, including: type, quantity; Asthma Quality of Life Questionnaire; laboratory efficacy indexes as the secondary outcome. General physical examination; routine examination of blood, urine, and stool; electrocardiogram; liver and kidney function examination; possible adverse reactions and related detection indicators as the security indexes. Meta-analysis will be performed using RevMan5.3.5 software provided by the Cochrane Collaboration. Results: This study will provide high-quality synthesis based on current evidence of Chinese medicines treatment for asthma in several aspects, including asthma control score, side effects and laboratory examination such as lung-function test, serum total immunoglobulin, and so on. Conclusion: The results of this study will provide updated evidence for whether Chinese medicines is an effective and safe intervention for asthma. PROSPERO registration number: PROSPERO CRD42019136074.